On the interplay between charge, spin and structural dynamics in transition metal complexes - Chergui, Majed (Dalton transactions : an international journal of inorganic chemistry, 2012)
This perspective presents some recent results concerning ultrafast intramolecular relaxation processes in metal-based molecular complexes. Ultrafast electronic/vibrational relaxation at sub-vibrational time scales, ultrafast intersystem crossing processes and ultrafast structure changes are discussed, stressing the questions that still need to be solved in order to arrive at a rationale that describes these processes. We will also discuss some new techniques, based on core-level spectroscopies that can provide new insights into the ultrafast intramolecular relaxation in these systems.